1997
DOI: 10.1002/(sici)1097-0185(199712)249:4<486::aid-ar8>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and structural characteristics of the reticular framework of the white pulp and marginal zone in the human spleen

Abstract: The reticular framework of the PALS, LF, and MZ is specialized into heterogeneous components in the human spleen. The heterogeneity of the framework may induce the segregation of T and B lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…At ultrastructural examination, reticulum cells display bundles of microfilaments (Pinkus et al 1986;Satoh et al 1997). A subpopulation of reticulum cells expresses the smoothmuscle isoform of actin (a-SMA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At ultrastructural examination, reticulum cells display bundles of microfilaments (Pinkus et al 1986;Satoh et al 1997). A subpopulation of reticulum cells expresses the smoothmuscle isoform of actin (a-SMA).…”
Section: Discussionmentioning
confidence: 99%
“…In human and rat spleen, a-SMAcontaining reticular cells were also demonstrated in the PALS; but in follicles, these cells were rare, corresponding to sparse reticulum cells and reticulin fibers in this area. FDCs may replace a-SMA-positive reticular cells in germinal centers (Toccanier-Pelte et al 1987;Satoh et al 1997Satoh et al ,2009Steiniger et al 2001). In vivo imaging has shown that the FDC network displays a marked mobility, and FDCs in culture express a-SMA (Bajénoff et al 2006;Muñoz-Fernández et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph follicles predominate in the human spleen whereas the PALS predominates in the rat (Steiniger et al 1997). The reticular framework of the white pulp is divided into 2 parts in mice (Tanaka et al 1996) and man (Satoh, 1997), one part surrounding the PALS and the other surrounding the lymph follicles. The marginal zone is the site of heavy blood traffic and filtration.…”
Section: mentioning
confidence: 99%
“…LSCM permits the examination of thicker slides than the ordinary LM does (Paddock 2000;Jirkovská et al 2005). Satoh et al (1997) used LSCM for recognition of white pulp stroma.…”
Section: Discussionmentioning
confidence: 99%